Advances in Communication Systems and Electrical Engineering - Huang, Xu. (Springer, 2017)
This volume contains revised and extended research articles written by prominent researchers participating in the IAENG International Conference on Communica- tion Systems and Applications, the IAENG International Conference on Internet Computing and Web Services, and the IAENG International Conference on Elec- trical Engineering of the MultiConference IMECS 2007. Topics covered include communications theory, communications protocols, network management, wireless networks, telecommunication, electronics, power engineering, signal processing, and industrial applications. The papers are representative of those subjects that sit on the top end of high technologies. The book offers state of the art advances in communication systems and electrical engineering and also serves as an excellent reference work for researchers and graduate students working with or in the com- munication systems and electrical engineering fields.